2022
DOI: 10.3390/pathogens11020243
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HBsAg Seropositivity among Pregnant Women Receiving Antenatal Care at 10 Community Health Centers in Freetown, Sierra Leone: A Cross-Sectional Study

Abstract: Hepatitis B (HBV) is a major public health threat in Sierra Leone. Pregnant women are disproportionately impacted, yet little is known about the epidemiology of HBV in this group. We conducted a cross-sectional study of pregnant women aged ≥16 years receiving antenatal care across 10 community health centers in Freetown from July to September 2021 to assess the prevalence and associated factors of HBsAg seropositivity. A logistic regression was used to identify the predictors of HBsAg seropositivity. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some previous studies have also demonstrated the significance of regional differences in the timely start of antenatal care and its utilization [18,19]. This is an unusual finding considering that the Western region of Sierra Leone is the most developed, has the liveliest economy, and has the biggest concentration of trained workers and medical facilities [20]. However, the Western regions are seeing an increase in the number of urban poor, who are unable to get adequate healthcare due to their high level of living and unequal access to social facilities [10].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Some previous studies have also demonstrated the significance of regional differences in the timely start of antenatal care and its utilization [18,19]. This is an unusual finding considering that the Western region of Sierra Leone is the most developed, has the liveliest economy, and has the biggest concentration of trained workers and medical facilities [20]. However, the Western regions are seeing an increase in the number of urban poor, who are unable to get adequate healthcare due to their high level of living and unequal access to social facilities [10].…”
Section: Discussionmentioning
confidence: 80%
“…However, the Western regions are seeing an increase in the number of urban poor, who are unable to get adequate healthcare due to their high level of living and unequal access to social facilities [10]. Additionally, the established staff issues in metropolitan areas, such as inadequate delegation, favoritism, and a lack of autonomy, may have an impact on the level of service provided by public health facilities, which further reduces the number of people who can access healthcare [20]. The trend observed in the eastern region could be attributed to the established processes for the opening, accreditation and closing of health facilities which were carried out across Sierra Leone as part of the National Health Sector Strategic Plan and the free maternal healthcare (2017-2021) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Survey questionnaire and stigma instrument development were informed by our experiences gained from interactions with PWHB in the clinical and community settings in Sierra Leone, our preliminary work describing the epidemiological, clinical, and social aspects of the HBV epidemic in Sierra Leone 11,29–33 and the broad literature on measuring HIV‐related stigma, 34,35 which has been adapted to inform studies in understanding HBV‐related stigma 4,5 …”
Section: Methodsmentioning
confidence: 99%
“…Survey questionnaire and stigma instrument development was informed by our experiences gained from interactions with PWHB in the clinical and community settings in Sierra Leone, our preliminary work describing the epidemiological, clinical and social aspects of the HBV epidemic in Sierra Leone [11,[29][30][31][32][33] and the broad literature on measuring HIV-related stigma [34,35], which has been adapted to inform studies in understanding HBV-related stigma [4,5].…”
Section: Instrument Development and Proceduresmentioning
confidence: 99%